A gamma-ray spectrometry analysis software environment. (April 2018) - Lutter, G.; Hult, M.; Marissens, G.; Stroh, H.; Tzika, F.
Abstract: At the JRC-Geel's RadioNuclide Metrology sector, a Monte Carlo code based on EGSnrc, and a general purpose calculation sheet implemented in Microsoft Excel ®, have been developed to make the quantitative gamma-ray spectrometry analysis of samples simpler and more robust. The further aim is that the software can be used by non-experts in gamma-ray spectrometry e.g. external researchers using JRC-Geel's facilities through the EUFRAT transnational access scheme. This paper presents the developed Monte Carlo software and the functionality included in the calculation sheet. Highlights: A Monte Carlo code has been developed and validated using EGSnrc. A radionuclide decay generator has been written and validated. Detection efficiency can be calculated for High Purity Germanium detector. A flexible and user friendly analysis software using MS Excel ® has been developed. Functionalities and performances of the software are presented.